Psychological Aspects of the Formation of Ethical Relationship in Preschool Children - Erkinovich, Parmonov Bobir (Indonesian Journal of Innovation Studies, 2022)
The article is a study of the problem of psychological features of the formation of moral behavior in preschool children on the basis of scientific, theoretical, methodological, socio-political sources, analysis of the current situation in practice. It describes how to define and justify the relationship between the concept of moral behavior in preschool children and the psychological and social moral characteristics of children.